Fluid dynamics characterization and thrombogenicity assessment of a levitating centrifugal pump with different impeller designs. (September 2020) - Bozzi, Silvia; Vesentini, Simone; Santus, Marco; Ghelli, Nicola; Fontanili, Paolo; Corbelli, Marco; Fiore, Gianfranco B.; Redaelli, Alberto C.L.
Highlights: Hypershear trigger platelet activation in blood recirculating devices. Lagrangian models can assess the thrombogenic potential of extracorporeal pumps. Impeller configuration affects vorticity dynamics and shear stress regimes. Impeller blade number impacts on platelet activation and blood stagnation. Abstract: Technical guidelines nowadays recommend and regulate the use Computational Fluid Dynamics (CFD) to assess the performance of medical devices. CFD coupled to blood damage models has emerged as a powerful tool to evaluate the hemocompatibility of blood recirculating devices. The present study is aimed at evaluating the hydrodynamic performance and the thrombogenic potential of two prototypes of magnetically levitating centrifugal pumps. The two devices differ in the impeller configuration - 6-blades vs. 12-blades – and have been designed to be used in Cardiopulmonary Bypass (CPB) circuits during open heart surgery and in Extracorporeal Membrane Oxygenation (ECMO) to support patients with severe cardiac or respiratory failure. The pumps have been modelled using Direct Numerical Simulation coupled to Lagrangian analysis to predict platelet activation due to abnormal shear stress histories. Numerical results have been compared with experimental data in terms of head generation for different working points. Results show that the 6-blades pump has i ) smaller stagnation areas, ii ) lower stress levels and iii ) higher strain rate, resulting in a lower thrombogenic potential, whereas the 12-blade impeller guarantees a more stable performance at high flow rates, suggesting its preferential use for more demanding applications, such as CPB.